The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4049/jimmunol.1102137
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Inhibition of IL-6 Trans-Signaling Protects from Malaria-Induced Lethality in Mice

Abstract: Circulating IL-6 levels correlate with the severity of blood-stage malaria in humans and mouse models, but the impact of IL-6 classic signaling through membrane IL-6Rα, as well as IL-6 trans-signaling through soluble IL-6Rα, on the outcome of malaria has remained unknown. In this study, we created IL-6Rα–deficient mice that exhibit a 50% survival of otherwise lethal blood-stage malaria of the genus Plasmodium chabaudi. Inducing IL-6 trans-signaling by injection of mouse recombinant soluble IL-6Rα in IL-6Rα–def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 25 publications
2
29
0
2
Order By: Relevance
“…However, when bound to the soluble receptor created, for example, by ectodomain shedding from the membranebound receptor, IL-6 is then also able to communicate, by trans-signaling, with all other cells through the ubiquitously expressed signal transducer GP130. There is evidence that inhibition of IL-6 trans-signaling protects from P. chabaudi malaria (Wunderlich et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…However, when bound to the soluble receptor created, for example, by ectodomain shedding from the membranebound receptor, IL-6 is then also able to communicate, by trans-signaling, with all other cells through the ubiquitously expressed signal transducer GP130. There is evidence that inhibition of IL-6 trans-signaling protects from P. chabaudi malaria (Wunderlich et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model of atherosclerosis, sgp130Fc did not only reduce disease, but led to a significant regression of advanced atherosclerosis, most probably through reduced monocyte recruitment and the progression of atherosclerotic plaques [16]. Inhibition of IL-6 trans-signaling was further shown to be protective in an otherwise lethal infection with Plasmodium chabaudi, which causes malaria [17]. The damaging effects of IL-6 in the central nervous system also appear to depend solely upon trans-signaling, as mice which express sgp130 under the GFAP promoter are fully protected [18 ].…”
Section: Il-6 Classic Versus Trans-signalingmentioning
confidence: 97%
“…and the second wave peaking at maximal parasitemia on day 8 p.i. (Wunderlich et al, 2012). In parallel, the liver biphasically produces mRNAs coding for IL-1β, TNFα, and IL-6 (Krücken et al, 2009).…”
Section: Liver Effectors Toward Blood-stage Malariamentioning
confidence: 99%
“…Conversely, decreasing IL-6 levels are reported to be associated with decreasing parasitemia (Sarthou et al, 1997) and hyperpyrexia (Seoh et al, 2003), as well as after anti-malarial treatment (Hugosson et al, 2006). In experimental murine malaria, it has been shown that IL-6 trans-signaling, rather than classic IL-6 signaling, contributes to malaria-induced lethality (Wunderlich et al, 2012). Indeed, approximately 50% of IL-6Rα-deficient mice survive an otherwise lethal P. chabaudi blood-stage malaria.…”
Section: Liver Effectors Toward Blood-stage Malariamentioning
confidence: 99%
See 1 more Smart Citation